KREATIVITAS SENGGAKAN CENDOL DAWET OLEH KELOMPOK MUSIK DANGDUT MG86 - Tantri, Dewi; Gendra Nata Utami, Fawarti (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2024)
The research entitled “CREATIVITY SENGGAKAN CENDOL DAWET BY MG86 music group” was moti vated by the problem of the uniqueness of the musical text Cendol Dawet, the text is an insert used to fill in one part of the melody of a song. Cendol dawet is a song phenomenon in songs. From this uniqueness, Cendol Dawet is popular in the community. This study aims to find out how the process of forming Senggakan Cendol Dawet, The presentation structure and influence resulting from the crush by the members of the Gila 86 Music group that can build the group to become popular.This research uses the theory of “creativity” from Rhodes in Utami Munandar’s book, namely in creating a creativity is always supported by person, process, perss, product. There are two stages of creativity formulation found in this study, where “senggakan cendol dawet” as a product of creativity formulation by the initiator transforms and is treated as a person in the next formulation of creativity. The formulation of creativity in the second stage produces products in the form of the impact of popularity, management, and move ment that overshadow the identity of the music group and its glory.Qualitative methods are used to obtain field data. Based on the results of the study, it can be concluded that Senggakan Cendol Dawet presents a hope in creating senggakan does not have to use the word riot which connotes pornography which serves to advance the image of dangdut music so that it can be loved and enjoyed by the commu nity. In addition, the role of Senggakan Cendol Dawet can liven up the atmosphere of the stage during performances and provide social life changes for members of the Gila 86 Music group.